Digitization of society: A survey of mobile home service recommender development / Noorfaizalfarid Mohd Noor and Nur Najihah Kamaruzaman - Mohd Noor, Noorfaizalfarid; Kamaruzaman, Nur Najihah (UiTM Cawangan Perlis, 2019)
Mobile home service recommender application offers smart and efficient interaction to unify digitally the multi background residents in the community to delineate their inhouse issues such as to get handyman for home service. The current process of getting home service need data that can be considered and matched according to the issue. Using embedded recommender logic inside the mobile application, it can match the resident's profile and problem preferences by analysing the behaviour of each item and finally generate personalized home service recommendation solution. This paper conducted a preliminary study in digitizing home service using recommender approach. It aims to investigate the current behaviour of people on getting home service and their readiness to use tailored mobile home service searching application. It collects data from 339 respondents using social media platform. The result from the survey shows that mobile application is common in people life. It also reveals that residents are commonly facing issues on piping, home appliance, furniture, gas cooking, baby care, grass and home maid. To get solution, people are very depending on home service. However, the current way of getting the home service is inadequate to assist them. It also disclosed that people prefer to use mobile application to improve the home service searching. Either conventional or advanced recommender, mobile application can provide on the go and portable service to produce home service personalized recommendation. As conclusion, this paper offering scholars with the state-of-the-art knowledge to embark the recommender approach for home service platform toward digitization of society.